2019
DOI: 10.4300/jgme-d-19-00218.1
|View full text |Cite
|
Sign up to set email alerts
|

See No Evil, Hear No Evil, Stop No Evil: Institutional-Level Tracking to Combat Mistreatment of Residents and Fellows

Abstract: Background Mistreatment of trainees, including discrimination and harassment, is a problem in graduate medical education. Current tools to assess the prevalence of mistreatment often are not administered institutionally and may not account for multiple sources of mistreatment, limiting an institution's ability to respond and intervene. Objective We describe the utility of a brief questionnaire, embedded within longer institutional program evaluations, measuring the prevalence of different types of trainee mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…10 Characterizing the nature and frequency of these occurrences may be particularly important for academic medical centers, as these incidents undermine learning for trainees and may result in delayed or suboptimal patient care. 3,4 Data on the frequency of these occurrences among trainees-and even more so on physicians' responses to them-are limited, as much of the literature consists of first-person physician accounts of interactions with racist patients or online surveys of practicing physicians. [5][6][7][11][12][13][14][15][16][17][18] A recent national survey of general surgery residents reported that 43% of residents experienced discrimination on the basis of gender identity and 47% experienced racial/ethnic discrimination from patients or patients' families.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Characterizing the nature and frequency of these occurrences may be particularly important for academic medical centers, as these incidents undermine learning for trainees and may result in delayed or suboptimal patient care. 3,4 Data on the frequency of these occurrences among trainees-and even more so on physicians' responses to them-are limited, as much of the literature consists of first-person physician accounts of interactions with racist patients or online surveys of practicing physicians. [5][6][7][11][12][13][14][15][16][17][18] A recent national survey of general surgery residents reported that 43% of residents experienced discrimination on the basis of gender identity and 47% experienced racial/ethnic discrimination from patients or patients' families.…”
Section: Introductionmentioning
confidence: 99%
“…Biased patient behaviors can range from offensive quips to outright refusal of care 3 and can exact a heavy psychological toll on physicians. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 It is possible that physicians’ encounters with biased patients have become more common in recent years: the health care workforce is increasingly diverse along multiple social dimensions, and the number of hate groups and hate crimes in the US has grown during the past 5 years, suggesting increased social polarization. 10 Characterizing the nature and frequency of these occurrences may be particularly important for academic medical centers, as these incidents undermine learning for trainees and may result in delayed or suboptimal patient care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humiliation and belittlement are the most frequently occurring forms of mistreatment for residents, and also the most distressing. [42][43][44] Humiliation and shame are found to be most perpetuated by departmental faculty for residents 2 and are expected as normal experiences during training. 45 Although approximately 22% of U.S. medical students graduating in 2020 reported being publicly humiliated at least once during their training, 46 there are no comparable data for U.S. residents.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing frequency of PPtP also at academic medical centers is important to document, especially where a diverse body of healthcare providers is providing care in less diverse settings. These occurrences pose a psychological toll on trainees, undermine learning opportunities, and may result in suboptimal patient care (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%